Automated microfluidic mixer for on-chip cell dissociation from 3D cell culture systems - Ong, Eunice Si Min (Nanyang Technological University, 2024)
Three-dimensional (3D) suspension cell culture (eg. Microcarriers or cell aggregates) in bioreactors is widely used in cell-based manufacturing due to its scalability and higher cell yield than conventional 2D monolayer cell culture methods. However, cell harvesting from bioreactors requires manual enzymatic cell dissociation from the microcarrier, membrane-based filtration and multiple washing steps which may cause significant cell loss. Herein, we present a novel 3D printed herringbone micromixer system for automated on-chip cell dissociation from microcarriers and cell aggregates. As a key criterion for cell dissociation is to ensure mixing of cell samples with an enzymatic solution (Trypsin), we first optimised the design on the staggered herringbone structure to induce chaotic turbulent flows by characterising the mixing performance using fluorescent dye (FITC) and water. Next, we custom built a miniatured pneumatic disc pump integrated with a micro-controller (in-house designed Arduino system) to provide portability and ease of integration with bioreactors. Using adipose-derived mesenchymal stem cell (ADSC) as a model cell line for 3D cell culture using microcarriers/cell aggregates, we demonstrated successful enzymatic dissociation of cells using the developed setup to achieve high yield and viability of the cells harvested. We envision this platform technology can be integrated directly to bioreactors to facilitate automated cell harvesting without any human intervention for continuous cell manufacturing applications.